Report of a Consensus Meeting on Human Brain Temperature After Severe Traumatic Brain Injury: Its Measurement and Management During Pyrexia - Childs, Charmaine; Lecky, Fiona; Wieloch, Tadeusz; Machin, Graham; Harris, Bridget; Stocchetti, Nino (Frontiers in Neurology, 2010)
Temperature disturbances are common in patients with severe traumatic brain injury. The possibility of an adaptive, potentially beneficial role for fever in patients with severe brain trauma has been dismissed, but without good justification. Fever might, in some patients, confer benefit. A cadre of clinicians and scientists met to debate the clinically relevant, but often controversial issue about whether raised brain temperature after human traumatic brain injury should be regarded as ‘good or bad’ for outcome The objective was to produce a consensus document of views about current temperature measurement and pyrexia treatment. Lectures were delivered by invited speakers with National and International publication track records in thermoregulation, neuroscience epidemiology, measurement standards and neurocritical care. Summaries of the lectures and workshop discussions were produced from transcriptions of the lectures and workshop discussions. At the close of meeting, there was agreement on four key issues relevant to modern temperature measurement and management and for undergirding of an evidence-based practice, culminating in a consensus statement. There is no robust scientific data to support the use of hypothermia